Electrical signalling in tomato — Oidium neolycopersici pathosystem for detection of powdery mildew - Matić, Slavica; Masoero, Giorgio; Egidi, Andrea; Francese, Claudio; Capra, Pier Paolo; Sosso, Andrea (Computers and electronics in agriculture, 2025)
Plants are subjected to a plethora of biotic stresses caused by various pathogens; among them, fungal pathogens represent the most destructive ones. In order to preserve the health status of plants, especially under the influence of climate change, the need to develop new sustainable, inexpensive, in-field and non-destructive diagnostic methods for plant pathogens is of great importance. In this direction, spectroscopic and molecular methods have made progress, while others, such as electrical diagnostic methods are still in the early stages of development. In this work, electrical signals in tomato plants infected with the fungal pathogen Oidium neolycopersici, the causative agent of powdery mildew, were measured. Differences in electrical responses were observed between healthy and infected plants during the entire monitoring period, and infected plants showed overall lower values of the electrical potential in comparison with healthy plants. Measurement of electrical potential allowed the successful differentiation between infected and healthy plants before the onset of symptoms (3.2 days in advance). A significant difference in electrical signals was obtained not only between infected and healthy plants, but also concerning the growing substrate: A stronger electrical potential was measured in plants grown in the peat-based substrate compared to those cultivated in the water substrate allowing a 97.5% discrimination. Based on the results of this study, measurements of electrical signals may become the basis for an alternative non-destructive diagnosis of tomato powdery mildew and other plant diseases. With the possibility of directly applying the technique in the field followed by remote monitoring of electrical signals, it may become useful for supporting timely disease control. •Electrical potential is different in healthy and powdery mildew-infected plants.•Differentiation is possible at 3.7 days before the visible onset of symptoms.•Plants grown in peat show greater electrical potentials from those grown in water.•Electrical potential can be used as alternative diagnostics for plant diseases.